Blooming from the Ash: How Survivors Revive from Volcano Eruption through Tourism in Merapi Volcano Region, Yogyakarta, Indonesia - Irawan, Popi (Journal of Indonesian Tourism and Development Studies, 2024)
Tourism in disaster-prone destinations should be carefully planned to mitigate potential impacts from imminent hazards that may result in catastrophic effects. This study explores how survivors of a volcanic eruption in Indonesia turn to tourism as a possible option to reclaim their livelihood. It also attempts to capture how local communities involved in the daily activities of tourism-related services get their economic benefits from tourism. Due to a volcanic eruption, the new landscape requires residents to shift their occupations from mainly agricultural-based jobs to service-based livelihood. This research applies a case study method, where the primarily data is obtained by a qualitative method with the social constructivism approach as its epistemological basis. The data is obtained using semi-structured interviews with selected participants determined by a purposive sampling technique. In addition to the qualitative data, this study enriches its discussion by administering a survey to local communities working directly in tourism using a purposive quota sampling method. This research shows that in terms of economic advantages, tourism impacts local communities positively regarding job opportunities and income. The shift of occupations, while easy for some residents who previously knew tourism, is a challenge for local people. Moreover, the economic advantages should not be the only consideration in developing tourism in disaster-prone destinations. One issue from this research is how community resilience can potentially be enhanced amidst the growing economic benefits and threats from potential hazards due to the eruption. Keywords: tourism, livelihood, disaster, economic benefits, volcano.